The Influence of Organic Matter on Soil Compactibility and Air Permeability of some Soils in Borno State - Mamman, E.; Ohu, J.O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
A laboratory experiment was conducted to determine the influence of an organic material (groundnut haulms) on the compactibility and air permeability of three most common agricultural soils (clay, sandy clay and sandy loam) in Borno state. The organic material was incorporated into the soils at three levels (2, 4 and 6% by mass of dry soil) and the soil-organic matter mixtures were compacted at three levels (5, 15 and 25 hammer blows). Incorporation of the organic material into the soils reduced their bulk densities and increased their air permeabilities. The bulk density for Ngala town clay, Nguma sandy clay and University sandy loam soils when incorporated with 2% organic matter and compacted using 25 hammer blows at 10% moisture content were 1.50, 1.59 and 1.74 Mgm-3 respectively. When the organic matter level was increased to 6% and compacted at 10% moisture content using 25 hammer blows, the bulk densities of the soils reduced to 1.41, 1.49 and 1.63 Mgm-3 for Ngala town clay, Nguma sandy clay and University sandy loam respectively. The air permeability for Ngala town clay, Nguma sandy clay and University sandy loam soils when incorporated with 2% organic matter and compacted using 25 hammer blows at 25% moisture content were 17, 23 and 37 μm² respectively. When the organic matter level was increased to 6% and compacted at 25% moisture content using 25 hammer blows, the air permeability of the soils increased to 28, 32 and 48 μm² for Ngala town clay, Nguma sandy clay and University sandy loam, respectively. For each level of organic material, air permeability of each soil decreased with increase in the number of hammer blows. Incorporation of the organic material into the clay soil increased its susceptibility to compaction and this resulted in much lower values of air permeability than in the sandy loam soil. Statistical models were generated to predict the air permeability of the soils in terms of silt and clay contents, moisture content, compaction and organic material levels. The implications of the results obtained in determining severity of compaction on these agricultural soils were discussed.